Genetic diversification patterns in swine influenza A virus (H1N2) in vaccinated and nonvaccinated animals - López-Valiñas, Álvaro; Valle, Marta; Pérez, Marta; Darji, Ayub; Chiapponi, Chiara; Ganges, Llilianne; Segalés, Joaquim.; Núñez, José I. (Frontiers in Cellular and Infection Microbiology, 2023)
Influenza A viruses (IAVs) are characterized by having a segmented genome, low proofreading polymerases, and a wide host range. Consequently, IAVs are constantly evolving in nature causing a threat to animal and human health. In 2009 a new human pandemic IAV strain arose in Mexico because of a reassortment between two strains previously circulating in pigs; Eurasian "avian-like" (EA) swine H1N1 and "human-like" H1N2, highlighting the importance of swine as adaptation host of avian to human IAVs. Nowadays, although of limited This is a provisional file, not the final typeset article use, a trivalent vaccine, which include in its formulation H1N1, H3N2, and, H1N2 swine IAV (SIAV) subtypes, is one of the most applied strategies to reduce SIAV circulation in farms. Protection provided by vaccines is not complete, allowing virus circulation, potentially favouring viral evolution.The evolutionary dynamics of SIV quasispecies were studied in samples collected at different times from 8 vaccinated and 8 non-vaccinated pigs, challenged with H1N2 SIV. In total, 32 SIV genomes were sequenced by next-generation sequencing, and subsequent variant-calling genomic analysis was carried out. Herein, a total of 364 de novo single nucleotide variants (SNV) were found along all genetic segments in both experimental groups. The non-synonymous substitutions proportion found was greater in vaccinated animals suggesting that H1N2 SIV was under positive selection in this scenario. The impact of each substitution with an allele frequency greater than 5% was hypothesized according to previous literature, particularly in the surface glycoproteins hemagglutinin and neuraminidase. The H1N2 SIV quasispecies evolution capacity was evidenced, observing different evolutionary trends in vaccinated and non-vaccinated animals.